Feminist Geopolitics. Issue 8 (2nd August 2013) - Massaro, Vanessa A.; Williams, Jill
Abstract: This paper traces the development of feminist geopolitics as a distinct analytical, epistemological, and methodological approach in geography. Feminist geopolitics is explained as an analytic approach that connects seemingly disparate people, places, events, and issues to show the connections across various operations of power and productions of inequality and exploitation. In so doing, we demonstrate the ways in which feminist geopolitics challenges the scales of geopolitics and refocuses on the mundane, everyday reproductions of geopolitical power. We further discuss recent work in the field that examines issues of security and insecurity to illustrate what insights can be gained by employing a feminist geopolitical framework.